دور الاستثمار السياحي في التنمية - يوسفي, أمال; بلمرداسي, يامن (جامعة الوادي - University of Eloued, 2020)
تهدف هذه الورقة البحثية للوقوف على واقع الاستثمار السياحي من خلال عرض مفهومه وأهميته والخصائص المميزة له، وكذا مجالات الاستثمار، وأهدافه مع محددات نموه. حيث يتبين من خلال نتائج هذه الدراسة ان الاستثمار السياحي يشمل الاستثمار في المقومات والامكانيات السياحية، التجهيزات، التسهيلات السياحية، ويساهم في مختلف عمليات التنمية، ويبقى يحتاج لتسهيلات مالية وحوافز بصورة مستمرة. This research paper aims at identifying the reality of tourism investment by presenting its concept, importance and distinctive characteristics, as well as investment fields, and its objectives with the determinants of its growth. Where it becomes clear through the results of this study that tourism investment includes investing in tourism potentials and capabilities, equipment, and tourist facilities, and contributes to various development operations, and remains in need of financial facilities and incentives on an ongoing basis.
Keywords: الاستثمار;الاستثمار السياحي;مجالات الاستثمار;قطاع السياحة;نم